Octopaminergic gene expression and flexible social behaviour in the subsocial burying beetle Nicrophorus vespilloides - Chris Cunningham (Insect Molecular Biology, 2014)
Flexible behaviour allows organisms to respond appropriately to changing environmental and social conditions. In the subsocial beetle Nicrophorus vespilloides, females tolerate conspecifics when mating, become aggressive when defending resources, and return to social tolerance when transitioning to parenting. Given the association between octopamine and aggression in insects, we hypothesized that genes in the octopaminergic system would be differentially expressed across different social and reproductive contexts. To test this in N. vespilloides, we first obtained the sequences of orthologues of the synthetic enzymes and receptors of the octopaminergic system. We next compared relative gene expression from virgin females, mated females, mated females alone on a resource required for reproduction and mated females on a resource with a male. Expression varied for five receptor genes. The expression of octopamine β receptor 1 and octopamine β receptor 2 was relatively higher in mated females than in other social conditions. Octopamine β receptor 3 was influenced by the presence or absence of a resource and less by social environment. Octopamine α receptor and octopamine/tyramine receptor 1 gene expression was relatively lower in the mated females with a resource and a male. We suggest that in N. vespilloides the octopaminergic system is associated with the expression of resource defence, alternative mating tactics, social tolerance and indirect parental care.